Peer review statement - - - (Universitas Sebelas Maret, 2017)
All papers published in this volume of International Journal of Science and Applied Science: Conference Series have been peer reviewed through processes administered by the proceedings Editors. Reviews were conducted by expert referees to the professional and scientific standards expected of a proceedings journal published by Sebelas Maret University.